Evaluation of the -318C/T (rs5742909) CTLA4 gene polymorphism influence on kidney function after transplantation - Veljančić, Nevena (Medicinski podmladak, 2022)
ABSTRACT  Introduction: CTLA-4 protein (Cytotoxic T Lymphocyte Antigen-4) is a molecule that plays a significant role in maintaining immunological homeostasis. Recent studies demonstrated an unequivocal proof that CTLA-4 has an inhibitory effect on immune response. CTLA4 gene has been identified with several single nucleotide polymorphisms which could change gene activity, consequently leading to structural protein change. This genetic variability is associated with acute rejection and delayed graft function as important indicators of kidney transplantation success.Aim: The aim of this study was to evaluate the potential association of CTLA4 (rs5742909) polymorphisms with acute rejection and delayed graft function in patients with kidney transplant.Material and methods: A total of 151 patient were included in this retrospective cohort study. Real-time polymerase chain reaction was used to determine the genotype which was then evaluated in relation to acute rejection and delayed graft function. Statistical significance was analyzed by Pearson's Chi-square and Fisher's exact test.Results: The most frequent genotype among 151 patient was CC (80.8%), then CT (17.9%) and TT (1.3%). The frequency of C allele is 89.7% whereas the frequency of T allele is 10.3%. There was no statistically significant difference in CTLA4 genotype and allele distribution nor their linkage to acute rejection and delayed graft function. The evaluation of C or T allele carriers showed no statistically significant difference with respect to previously mentioned posttransplant complications. Conclusion: In this study, no statistically significant association between -318C/T (rs5742909) CTLA4 polymorphism and AR/DGF was found.
Keywords: CTLA4, polymorphism, acute rejection, delayed graft function